Altered Selective Attention or Increased Imagination: Effects of Eye Closure on Vocal Expression Perception. - Jiang, Xiaoming; Luo, Renneng; Yang, Qi (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study investigated how eye closure (EC) affects vocal expression perception, testing two hypotheses: Hypothesis 1 proposes that EC enhances selective attention to task-related cues while suppressing prosodic processing, predicting higher expressiveness ratings for full (unmodified) versus filtered (acoustically degraded stimuli under eye-closed conditions) stimuli. Hypothesis 2 posits that EC activates compensatory imagination, expecting filtered (semantically neutral) stimuli to elicit higher ratings than full stimuli. Method: Forty listeners completed three tasks: sound verification task (detecting probe sounds), confidence rating task (evaluating listener-perceived confidence levels), and expressiveness rating (assessing emotional expressiveness) under EC and eyes-open (EO) conditions across full and filtered auditory modes. Results: The findings supported Hypothesis 1: EC led to significantly higher confidence and expressiveness ratings than the EO condition. Filtered stimuli received lower ratings than full stimuli across tasks, suggesting that EC enhanced selective attention to vocal prosody without engaging imaginative compensation (Hypothesis 2). Notably, EC did not affect sound verification hit rates, implying that its facilitative effects are more salient in cognitively demanding tasks (e.g., subjective ratings) than basic sound detection. Conclusions: These findings demonstrate that EC enhances vocal perception primarily through selective attention mechanisms, not imagination. The study advances theoretical understanding of EC's role in modulating attentional allocation during vocal processing, while highlighting (a) cognitive effects of shortterm visual deprivation on auditory perception and (b) dynamic cross-modal interactions between visual withdrawal and acoustic cue integration during speech comprehension.